Finding the needle in the haystack: systematic identification of psychobiotics. (18th January 2018) - Bambury, Aisling; Sandhu, Kiran; Cryan, John F; Dinan, Timothy G
Abstract : The brain–gut–microbiota axis is increasingly viewed as a novel paradigm in neuroscience with the capacity to generate innovative therapies for patients with psychiatric illnesses. Psychobiotics, defined as live bacteria, which when ingested in adequate amounts, confer mental health benefits, are increasingly of interest, as preclinical trials continue to show promising results. Particularly in stress‐related, anxiety and depressive disorders, there is potential for psychobiotics to deliver new therapies. The question of which microbes may prove to be the most promising psychobiotic in delivering such therapies at a clinical level is of great importance. Here we look at the characteristics of psychobiotics, in an attempt to present an outline from which the identification of potential new psychobiotics may be possible. Linked Articles: This article is part of a themed section on When Pharmacology Meets the Microbiome: New Targets for Therapeutics? To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.24/issuetoc